Media interaktif dalam meningkatkan media relations di hotel Novotel bandar lampung (Jurnal Kajian Media, 2020)
The development of information technology has a big impact in all areas of life, including in the world of public relations. To reach an audience that is spread all over the country, a Public Relations person needs both mass media and digital media to establish good relations with the media. A good relationship with the media will brings up good news in the mass media, which in turn will have an impact on the good image of an institution. This also applies to the Novotel Lampung hotel. The purpose of this paper is to map an interactive media model inimproving media relations activities at the Novotel Lampung hotel. This paper is based on the results of research conducted using a qualitative approach, a case study research design. The results of this study are first, media relations activities at the Novotel Lampung hotel are carried out through Media Gathering, Press Release, Press Tour, Press Conference, Social Media and collaboration with Mainstream Media. Second, Public Relations at this hotel has a role in shaping public opinion and a positive image of the agency, through media relations activities carried out.Third, the interactive media model in media relations activities at Novotel is a model of using applications that suit the needs of the field using Whatsapp, Website, Gmail, Google Drive and Google Calendar. Keywords: Media Relations; Media Interactive; Public Relations; Novotel Bandar Lampung.